Nexus Between Social Media and Brand Preference of Smart Mobile Phones: An Empirical Study in Sri Lanka - Vasanthakumar, K. (University of Jaffna, 2021)
The aim of the research is to evaluate the impact of social media marketing (with special reference to Facebook) on the brand preference of customers with regard to smart mobile phones. Since Facebook has become very popular today and a trend has arisen to use social media as a marketing tool, the researcher intended to evaluate the impact of social media marketing on brand preference, as the findings would provide valuable insight for future businesses. Social media as measured social media visibility, social media engagement, and social media influencewas the independent variableand brand preference was the dependent variable. The convenience sampling method was used where the sample was taken from a group of people easy to contact or to reach. A sample of 186 young males and females was selected. Factor loading and factor analysis were used to analyze the data and find the most influencing factors on brand preference. Reliability analysis, validity analysis, and regression analysiswere performed to analyze the data. The R2 value is 0.320 implying that 32.00% of the variance in brand preference is explained by social media influence, social media engagement, and social media visibility. The findings show thatsocial media visibility, social media engagement, and social media influencehave a positive impact on brand preference
Keywords: Social media; Facebook; Brand preference; Social media visibility; Social media engagement; Sri lanka